Designing An Environmental Communication Model For The Development Of Local Wisdom Based Ecotourism In Baduy Village Lebak Regency - Arfian Suryasuciramdhan; Asnawi Asnawi; Mohamad Ikrom (Jurnal Mamangan, 2024)
Good environmental communication will ensure that this local wisdom not only becomes a tourist attraction, but also remains alive and respected by tourists and the Baduy community itself. In the context of sustainable development, ecotourism based on the preservation of nature and local culture is a potential alternative. However, the development of ecotourism often poses a threat to cultural and environmental integrity if it is not managed in a communicative and participatory manner. The purpose of this study is to analyze the design of an environmental communication model in the development of ecotourism in Baduy Village based on local wisdom and to optimize economic benefits for the local community. It is hoped that ecotourism in this area can develop sustainably without disturbing the cultural values that have been passed down from generation to generation. The methodology used is a descriptive qualitative approach through observation, interviews, focus group discussions, and documentation presented in the form of data. The results and discussion in the environmental communication model consist of five elements, namely primary communication, messages, media/channels, communicants, and communication effects. The environmental communication model plays a central role in supporting the development of eco-tourism based on local wisdom in Baduy Village. Environmental communication not only helps preserve traditional values but also ensures that the growing tourism industry benefits the local community while maintaining environmental sustainability